Assessment of early-age cracking of high-performance concrete in restrained ring specimens - Quang-phu Nguyen; Lin-hua Jiang; Qiao Zhu (Water Science and Engineering, 2010)
High-performance concrete (HPC) is stronger and more durable than conventional concrete. However, shrinkage and shrinkage cracking are common phenomena in HPC, especially early-age cracking. This study assessed early-age cracking of HPC for two mixtures using restrained ring tests. The two mixtures were produced with water/binder mass ratio (mW/mB) of 0.22 and 0.40, respectively. The results show that, with greater steel thickness, the higher degree of restraint resulted in a higher interface pressure and earlier cracking. With steel thickness of 6 mm, 19 mm, and 30 mm, the age of cracking were, respectively, 12 days, 8 days, and 5.4 days with the mW/mB = 0.22 mixture; and 22.5 days, 12.6 days, and 7.1 days with the mW/mB = 0.40 mixture. Cases of the same steel thickness show that the ring specimens with a thicker concrete wall crack later. With the mW/mB = 0.22 mixture, concrete walls with thicknesses of 37.5 mm, 75 mm, and 112.5 mm cracked at 3.4 days, 8.0 days, and 9.8 days, respectively; with the mW/mB = 0.40 mixture, the ages of cracking were 7.1 days, 12.6 days, and 16.0 days, respectively.